La lutte intégrée contre l'acarien vert (Mononychellus Tanajoa (Bondard) du manioc (Manihot asculenta Crantz) au Burundi. - Ndayiragije, Pascal. (University of Ottawa (Canada), 1992)
Of 40 identified phytoseiid mites which occur in Burundi, only Eseius fustis was regularly observed on cassava, whereas E. talinga and E. bwende were rarely present. Iphiseius degenerans was also observed but not as frequently as E. fustis. Predatory insects (Holobus fageli, H. pallidicornis, Stethorus aethiops, S. fujunus and some families like Chrysopidae, hemerobiidae and Anhocoridae) were recorded on cassava during CGM outbreaks. Of two predatory phytoseiids introduced (Typhlodromalus limonicus and Neoseiulus idaeus) and released twice during the study period on two varieties of cassava (Nakarasi and Mpambayabashengera), only one was recovered in the rainy season when the CGM population is normally low. This may indicate its potential use as a biological control agent. Mean mite densities, leaf damage, pubescence and leaf cyanide content of twenty cassava varieties were evaluated for resistance. Pubescence was negatively correlated with leaf damage (r = $-$0,46; p 0.05) whereas no relation was found between cyanide and leaf damage. (Abstract shortened by UMI.)
Keywords: Agriculture, Agronomy.